9-Aminoacridinium bis(pyridine-2,6-dicarboxylato-κ(3) O (2),N,O (6))ferrate(III) tetrahydrate - Mirzaei, Masoud (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, (C(13)H(11)N(2))[Fe(C(7)H(3)NO(4))(2)]·4H(2)O, contains a 9-aminoacridinium cation, one anionic complex and four uncoordinated water molecules. In the anionic complex, the Fe(III) ion is six-coordinated by two almost perpendicular [dihedral angle = 88.78 (7)°] pyridine-2,6-dicarboxylate ligands in a distorted octahedral geometry. In the crystal, anions are connected into chains along [10-1] by weak C—H⋯O interactions, which create ten-membered hydrogen-bonded R (2) (2)(10) rings. These chains are linked by three-membered water clusters. The final three-dimensional network is constructed by numerous intermolecular O—H⋯O and N—H⋯O interactions.